Employer Branding Strategies Effects on Job Pursuit Intention of Business School Undergraduates: Case Study of Oil Companies in Indonesia - Devina, Monica; Retno Astrini, Melia; Syaebani, Muhammad Irfan (Journal of Entrepreneurship, Business and Economics, 2016)
Employers in Indonesia must set themselves apart from competitors to attract high quality graduates from the university since the competition for talent is so high. Therefore, employer needs to increase the value of company as a good employer by conducting early-recruitment branding strategies. This study aims to examine the impact of employer branding strategies and perceived job attributes of employer image towards organizational prestige and job pursuit intention. This paper also reveals the differences between those variables, which carried out by two oil companies in Indonesia with differ-ent characteristics. The one is state-owned oil company, and another one is multinational oil compa-ny. The respondents of this study are undergraduate students of Faculty of Economics and Business in one of the reputable university in Indonesia. Using structural equation modeling method, the results show that for state-owned oil company, word of mouth endorsement is the most significant dimension affecting perceived job attributes of employer image. While for multinational oil company, advertis-ing is the most significant dimension affecting perceived job attributes of employer image. Three of four employer image dimensions (working atmosphere, payment attractiveness, and task attractive-ness) influence organizational prestige, which in turn influences job pursuit intention for both compa-nies. The paper discusses the implication of the results for academic and company in the oil industry. Research paper Reference to this paper should be made as follows: Devina. M., Astrini, M. R., Syaebani, M. I. (2016). “Employer Branding Strategies Effects on Job Pursuit Intention of Business School Under-graduates: Case Study of Oil Companies in Indonesia”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 2, pp. 1–39